2022
DOI: 10.1007/s00737-022-01243-7
|View full text |Cite
|
Sign up to set email alerts
|

Two are better than one? The impact of lay birth companions on childbirth experiences and PTSD

Abstract: Although continuous support during childbirth is recommended by the World Health Organization (WHO) and has wellestablished benefits, the practice is still not routinely implemented in all maternity settings. We studied the possible effect of an additional lay companion (other than the partner) on childbirth experience and postpartum post-traumatic stress disorder (PTSD). Two hundred and forty-six women, who gave birth in maternity wards of a large tertiary health center in Israel, responded to questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
0
0
Order By: Relevance
“…Furthermore, we show that both PP-PTSD symptoms and subjective rates of traumatic birth experience were lowest among women who had both their partner and a doula or private midwife present at birth, which is supported by a previous study where authors show similar results as our findings, with higher PP-PTSD symptoms among women with a single companion compared to those with two or more companions [46]. Thus, allowing more than one person to accompany women during childbirth may be a simple and cost-effective approach for providing support in all birth settings and minimizing the incidence of PP-PTSD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we show that both PP-PTSD symptoms and subjective rates of traumatic birth experience were lowest among women who had both their partner and a doula or private midwife present at birth, which is supported by a previous study where authors show similar results as our findings, with higher PP-PTSD symptoms among women with a single companion compared to those with two or more companions [46]. Thus, allowing more than one person to accompany women during childbirth may be a simple and cost-effective approach for providing support in all birth settings and minimizing the incidence of PP-PTSD.…”
Section: Discussionsupporting
confidence: 92%
“…According to a Greek study, women with insufficient perinatal support from their partners were more likely to suffer from PTSD or PTSD symptoms after a cesarean birth than women who received adequate support from their spouses [45]. Furthermore, Handelzalts et al [46] found that participants who were supported by their partners and a second companion had fewer PP-PTSD symptoms than women who were accompanied only by their partners. Accordingly, several Russian studies showed that although there were no significant direct associations between support during labor and PP-PTSD, support from a partner, doula, or private midwife during childbirth was associated with lower rates of obstetric violence, fewer medical interventions, and higher birth satisfaction, which may indirectly mitigate the risk of PP-PTSD [20,24,47].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the expectations of birth companions. Studies have shown a variation in the expectations of birth companions [22,23]. The present study showed that birth companions expected their clients to respect cultural beliefs.…”
Section: Expectations For Birth Companionssupporting
confidence: 50%
“…Handelzalts (2022) [75] Israel PL BC PTSD Women who were accompanied by their partners and an additional companion were lower in birth-related PTSD symptoms than women accompanied by only their partner (p < 0.05). Jones (2018) [82] 295 USA R SES PPD Residential stability was found to be statistically significantly associated with PPD symptom severity based on the 3-month EPDS total score (p = 0.01).…”
Section: Resultsmentioning
confidence: 99%